1998
DOI: 10.1016/s1074-7613(00)80554-3
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Autoimmune Traits: Lyn, CD22, and SHP-1 Are Limiting Elements of a Biochemical Pathway Regulating BCR Signaling and Selection

Abstract: A B lymphocyte hyperactivity syndrome resembling systemic lupus erythematosus characterizes mice lacking the src-family kinase Lyn. Lyn is not required to initiate B cell antigen receptor (BCR) signaling but is an essential inhibitory component. lyn-/- B cells have a delayed but increased calcium flux and exaggerated negative selection responses in the presence of antigen and spontaneous hyperactivity in the absence of antigen. As in invertebrates, genetic effects of loci with only one functional allele can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
329
2
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(357 citation statements)
references
References 49 publications
25
329
2
1
Order By: Relevance
“…Under these circumstances, some of the factors causing a breakdown in tolerance could be antigen independent. Lyn-deficient B cells expressing Ig transgenes for hen egg lysozyme show increased differentiation to plasma cells even in the absence of lysozyme, which is consistent with a polyclonal B cell activation [29,54]. This process could be driven to affinity maturation and isotype class switching by antigen and TLR-dependent signals or by nonspecific activation of DC and hypersecretion of cytokines, such as IL-6.…”
Section: Discussionsupporting
confidence: 58%
“…Under these circumstances, some of the factors causing a breakdown in tolerance could be antigen independent. Lyn-deficient B cells expressing Ig transgenes for hen egg lysozyme show increased differentiation to plasma cells even in the absence of lysozyme, which is consistent with a polyclonal B cell activation [29,54]. This process could be driven to affinity maturation and isotype class switching by antigen and TLR-dependent signals or by nonspecific activation of DC and hypersecretion of cytokines, such as IL-6.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies using Lyn-deficient mice have shown Lyn to play an essential role in maintaining signaling thresholds in B cells [21,25,26], myeloid cells, including in mast cells [14,19,[34][35][36][37]. Loss of Lyn results in reduced activation of phosphatases, such as SHIP, which results in hypersensitivity to cytokines [19,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Lyn results in reduced activation of phosphatases, such as SHIP, which results in hypersensitivity to cytokines [19,24,25]. In both B cells as well as mast cells, loss of Lyn results in hyperactivation of AKT and the mitogen-activated protein kinase extracellular signal-regulated kinase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with this notion, studies of compound heterozygote mice have revealed the importance of threshold levels of proteins in controlling immune responses. 8,9 The phosphatidylinositol 3-kinase (PI3K) pathway which is activated following BCR and TCR stimulation 10,11 is well poised to regulate immune responses through antigen receptor signalling via the generation of phosphatidylinositol (3,4) bisphosphate (PIP 2 ) and phosphatidylinositol (3,4,5) trisphosphate (PIP 3 ). These reaction products allow translocation of multiple pleckstrin homology (PH) domain-containing proteins to the membrane, and these in turn regulate downstream events such as proliferation, apoptosis, protein synthesis, and cell shape (reviewed in Chan et al 12 and Martin 13 ).…”
Section: Introductionmentioning
confidence: 99%